The interrelationship of orthodontic tooth movement in patients with periodontitis and Diabetes mellitus - Bernardo, Daniella Vicensotto [UNESP]; Guimarães, Glaucio Serra; Camargo, Gabriela Alessandra Da Cruz Galhardo (Faculdade São Leopoldo Mandic, 2024)
Orthodontic tooth movement is a mechanically induced bone remodeling process aimed at aligning malpositioned teeth. Periodontitis is a polymicrobial infection of the supporting tissues of the teeth that results in the destruction of the periodontium. Diabetes Mellitus is a metabolic disorder that contributes to several types of comorbidities and even premature death of an individual. Due to the high demand of diabetic patients with periodontitis and the need for orthodontic therapy to achieve better periodontal health, we aimed to carry out a bibliographic review on orthodontic tooth movement in patients with periodontitis and diabetes mellitus. The search for articles in this literature review took place between February 2022 and March 2023. The articles were researched, selected and extracted through the database: PUBMED, LILACS and GOOGLE SCHOLAR available online, in the range of years between 1990 and 2022. Diabetes and periodontitis may adversely affect bone remodeling in orthodontic tooth movement. However, despite the need for further long-term studies to elucidate the mechanism of orthodontic tooth movement in diabetic patients with a history of periodontitis, the literature suggests that if there is a well-established periodontal-orthodontic therapy associated with the patient’s glycemic control, the treatment will be successful.

A movimentação dentária ortodôntica é um processo de remodelação óssea induzida mecanicamente com o objetivo de alinhar dentes mal posicionados. A periodontite é uma infecção polimicrobiana dos tecidos de suporte dos dentes que resulta na destruição do periodonto. O Diabetes Mellitus é um distúrbio metabólico que contribui para vários tipos de comorbidades e até mesmo a morte prematura de um indivíduo. Devido a grande demanda de pacientes diabéticos com periodontite e apresentando a necessidade da terapia ortodôntica para atingir melhor saúde periodontal, tivemos como objetivo realizar uma revisão bibliográfica sobre a movimentação dentária ortodôntica em pacientes com periodontite e diabetes mellitus. A busca pelos artigos desta revisão de literatura ocorreu entre fevereiro de 2022 e março de 2023. Os artigos foram pesquisados, selecionados e extraídos por meio das bases de dados: PUBMED, LILACS e GOOGLE SCHOLAR disponíveis online, no intervalo entre 1990 até 2022. Diabetes e periodontite podem afetar adversamente a remodelação óssea na movimentação dentária ortodôntica. No entanto, apesar da necessidade de mais estudos a longo prazo para elucidar o mecanismo da movimentação dentária ortodôntica em pacientes diabéticos com histórico de periodontite, a literatura nos sugere que se houver uma terapia periodontal-ortodôntica bem estabelecida associada ao controle glicêmico do paciente, o tratamento será bem-sucedido.
A inter-relação do movimento dentário ortodôntico em pacientes com periodontite e Diabetes mellitus
Keywords: Diabetes Mellitus; Orthodontics; Periodontitis; Diabetes Mellitus; Ortodontia; Periodontite